Laparoscopic assisted ERCP in patient with Roux-en-Y gastric bypass. A case report. (April 2021) - Mazzeo, Carmelo; Badessi, Giorgio; Pallio, Socrate; Viscosi, Francesca; Cucinotta, Eugenio
Highlights: Choledocholithiasis in Roux-en-Y patients is a therapeutic challenge for both surgeons and endoscopists. Prophylactic cholecystectomy is not recommended in bariatric surgery. Laparoscopic assisted-ERCP is a safe and feasible intervention. B-ERCP and EDGE are two valid alternatives B-ERCP and EDGE are two valid alternatives. Abstract: Introduction: Choledocholithiasis in Roux-en-Y patients is a therapeutic challenge for both surgeons and endoscopists. In fact, typical procedures, such as ERCP, can't be performed due to the altered anatomy of the patient. Nowadays, procedures on this kind of patient are performed not only in specialized bariatric centers, but, due to the increasing number of patients undergoing bariatric surgery, are starting to become more common even in smaller and non-specialized centers that don't possess the same expertise and technology. Case presentation: We present the case of a 33-year-old patient, who had already undergone bariatric surgery, and presented to our department with a diagnosis of choledocholithiasis. Due to the altered anatomy the patient was treated through a laparoscopic assisted ERCP. Discussion: A review of the need and proper timing for a cholecystectomy in this kind of patient, in order to prevent choledocholithiasis, is discussed. Moreover, a review of the literature regarding the possible treatments of this pathology in bariatric patients underlines the presence of other treatments, beyond the one performed in our department, that can be performed even in small non-specialized centers. Conclusions: Prophylactic cholecystectomy is not recommended in bariatric surgery. Laparoscopic assisted-ERCP is a safe and feasible intervention which is to be preferred, even if B-ERCP and EDGE are two valid alternatives.